AB0575 Retrospective survey of concomitant autoimmune diseases and autoantibodies in a cohort of patients with anca-associated vasculitis (AAV). (15th June 2017) - Moura, M Casal; Prieto-González, S; Espígol-Frigolé, G; Murgia, G; Alba, M; Hernández-Rodríguez, J; Cid, M
Abstract : Background: Anti-neutrophil cytoplasmic antibodies (ANCA) associated vasculitis (AAV) – granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA) have heterogenous clinic and biologic phenotypes. Sporadic reports indicate that some AAV patients may have other autoimmune diseases but the frequency of the association is unknown. Objectives: Our purpose was to assess the frequency of other autoimmune diseases or autoantibodies in a well-defined cohort of AAV patients. Methods: Retrospective survey of a cohort of patients regularly controlled at outpatient facility of an Autoimmune Disease Department in a 5-year period (2011–2016). Clinical and immunologic data were retrieved from electronic records. All patients were diagnosed and treated by the authors. Results: We included 110 AAV patients – 36 (32.7%) GPA, 45 (40.9%) MPA and 29 (26.4%) EGPA. Regarding to ANCA specificity – 23 (20.9%) against proteinase 3 (PR3)-ANCA, 68 (61.8%) against myeloperoxidase (MPO)-ANCA and 19 (17.3%) were ANCA negative. Organ-specific auto-immune diseases was actively searched in 73 (81.1%) patients and was present in 43 (58.9%) patients. More prevalent autoimmune diseases diagnosed were: hypothyroidism (15, 34.9%), pernicious anemia (12, 27.9%), Sjögren syndrome (8, 18.6%), hyperthyroidism (4, 9.3%) and primary biliar cholangitis (3, 7.0%). Autoantibodies more frequently positive were: ANAs 29 (67.4%), ASMA 27 (62.8%), anti-parietal cells 20 (46.5%), anti-thyreoglobulin 6 (14.0%), anti-peroxidase 12 (27.9%), anti-SSa 5 (11.6%), anti-SSb 3 (7.0%) and RF 14 (32.6%). Prevalence of organ-specific autoimmune disease was higher in MPA (67.4vs.32.6%, p=0.001) and ANCA-MPO carriers (81.4vs.18.6%, p<0.001). Pernicious anemia was more prevalent in MPA (41.4vs.0%, p=0.027) and in ANCA-MPO (34.3vs.0%, p=0.054) and myositis was more prevalent in ANCA-PR3 (12.5vs.0%, p=0.037). ANAs positivity was more prevalent in ANCA-MPO carriers (74.3%vs.36.5%, p=0.048). Predictive factors for development of organ-specific autoimmune disease identified were: female gender (OR 2.710, 95% CI 1.034–7.099, p=0.043), MPA syndrome (OR 3.578, 95% CI 1.334–9.523, p=0.011) and MPO carriers (OR 3.346, 95% CI 1.166- 9.601, p=0.025). Conclusions: A substantial percentage of AAV patients, particularly MPA and anti MPO carriers, have associated autoimmune diseases and autoantibodies. The limitations of our study (retrospective assessment and lack of comparator) do not allow accurate estimation of prevalence. The severity of AAV and difficulties in management, may lead to overlooking of associated autoimmune diseases which appear to be frequent. Associated autoimmune disease may contribute to additional burden in AAV patients. (Supported by SAF 2014 57708-R). Disclosure of Interest: None declared